2010
DOI: 10.1039/b926818a
|View full text |Cite
|
Sign up to set email alerts
|

Site-specific functionalisation of proteins by a Staudinger-type reaction using unsymmetrical phosphites

Abstract: Unsymmetrical phosphites react efficiently in a Staudinger reaction with p-azido-phenylalanine, which can be applied for the biotinylation of proteins, thereby expanding the scope of the chemoselective Staudinger-phosphite reaction of aryl azides with symmetrical phosphites to the corresponding phosphoramidates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 36 publications
0
48
0
2
Order By: Relevance
“…[44] Introducing azide-containing amino acids in this way, followed by Staudinger ligation has been successfully applied by various research groups. [45,46] An elegant example was reported by Yokoyama and co-workers, who used the amber stop codon to introduce p-azido-l-phenylalanine. It was then shown that after incorporation of the non-natural amino acid, modification of the azide unit could be accomplished by the Staudinger ligation.…”
Section: Non-natural Amino Acidsmentioning
confidence: 99%
See 2 more Smart Citations
“…[44] Introducing azide-containing amino acids in this way, followed by Staudinger ligation has been successfully applied by various research groups. [45,46] An elegant example was reported by Yokoyama and co-workers, who used the amber stop codon to introduce p-azido-l-phenylalanine. It was then shown that after incorporation of the non-natural amino acid, modification of the azide unit could be accomplished by the Staudinger ligation.…”
Section: Non-natural Amino Acidsmentioning
confidence: 99%
“…[47] The Staudinger ligation, as described in the examples above, requires a two-step procedure for the visualization of the target compound. This process could be simplified to a single-step method through the design of a Staudinger probe containing a fluorogenic coumarin moiety (46). [48] Prior to ligation, the coumarin-phosphine dye is nonfluorescent as a result of quenching of the excited state of the fluorophore by the lone pair of electrons on the phosphorus atom (Scheme 11 a).…”
Section: Non-natural Amino Acidsmentioning
confidence: 99%
See 1 more Smart Citation
“…41 Furthermore, P(O)─Cl bond formation has also been investigated via Michaelis-Arbuzov rearrangement of trialkyl phosphite with Cl 2 . [47][48][49][50] This synthesis procedure involves the reaction of alkyl azides with trialkyl phosphite to produce phosphorimidates, followed by rearrangement to their corresponding phosphoramidates. However, upscaling of these synthetic procedures is challenging because of their exothermic nature, expensive raw material as well as side products and moderate reactions yields.…”
Section: General Synthesis Methodsmentioning
confidence: 99%
“…REVIEWWILEYONLINELIBRARY.COM/APP Phosphortriamidates 41 and 42 were synthesized by reaction of triethyl phosphate with an excess of ethylene diamine and benzene-1,3-diamine, respectively (Scheme 4). A series of phosphorus nitrogen containing Compounds(43)(44)(45)(46)(47)(48) as shown infigure 10were prepared from phenylphosphonic dichloride and different amines in the presence of triethylamine (TEA) as a base. Their FR behaviors were investigated, and UL-94 tests showed that for the EPs with 2 wt % P a V-0 rating and LOI values of 30% could be achieved 96.…”
mentioning
confidence: 99%